Tradisi Bararak Anak Pancar Dalam Upacara Adat Perkawinan Masyarakat Rantau Kuantan Kabupaten Kuantan Singingi - indra putra, edi susrianto; Surya, Roberta Zulfhi (Jurnal Edukasi, 2024)
The tradition in this study refers to customs, beliefs, habits, and other things inherited in descent. These inherited customs encompass a variety of cultural values that include customs, social systems, knowledge systems, languages, arts, belief systems and so on. The aim of this research is to find out the traditional shape of the barak boy pancar that exists in the area of Kuantan Rantau and the cultural values that exist in it. This research uses a qualitative approach with descriptive methods. Data collection is done through observations, interviews, documentation and literature studies. The tradition of bararak son pancar is one of the forms of tradition that exists in Malay society which contains very high cultural values. Cultural values become guidelines of behavior for a society of one generation to the next. This process makes cultural values continue to be preserved and inherited by society downward.